Beyond Spiritual Ritual: Qur’anic Khataman as a Catalyst for Socio-Economic Solidarity in Rural Indonesia - Kharir, Agus; Lizamah, Mawaddatul (Surau Journal of Islamic Studies, 2025)
This study examines the dual role of Qur’anic khataman tradition at Ihsanul Ato Mosque in Sumenep, Indonesia, as both a spiritual practice and a mechanism for socio-economic solidarity. Through an exploratory qualitative approach—using in-depth interviews, participatory observation, and document analysis—the research reveals how khataman transcends its religious function to foster community resilience. Findings indicate that khataman integrates weekly arisan (rotating savings scheme) into its structure, creating an informal economic network that supports collective needs such as healthcare, education, and small-business capital. Simultaneously, it serves as a vital social space where villagers across ages and professions strengthen communal bonds, share information, and provide moral support. The tradition bridges Islamic spirituality with local socio-cultural values like gotong royong (mutual cooperation), transforming the mosque into a dynamic hub for holistic community development. Participants report enhanced social cohesion, economic reciprocity, and intergenerational transmission of Qur’anic values such as sincerity and solidarity. However, the study’s single-site focus limits broader generalizability, and future research should explore variables like gender dynamics and local leadership. This research contributes to socio-religious studies by demonstrating how grassroots religious practices can drive sustainable socio-economic empowerment. It challenges reductionist views of khataman as merely ritualistic, positioning it instead as a adaptive strategy for resource-scarce rural communities. Policymakers may leverage such indigenous traditions to design culturally resonant social programs in Muslim-majority contexts.